Analisis Efisiensi Pembakaran pada Burner Berbahan Bakar LNG dalam Menghasilkan Uap Panas - Vini Noviani; Tarya; Yosa Nizar Fernanta; Choirul anwar; Amri Abdulah; Irwan Suriaman (Jurnal Teknologika, 2025)
The burner in the Continuous Sheet Line (CSL) machine plays a crucial role in generating heat for the steel production process. However, under operational conditions, problems such as explosion and imperfect combustion are often found due to imperfect air-gas ratios. This study aims to analyze the performance of LNG-fueled burners in CSL furnaces, evaluate the influence of Air Flue Ratio (AFR), air and gas distribution on combustion efficiency in each zone, and assess the role of casing materials as insulators on furnace thermal efficiency. The data studied included gas and air pressure, flow rate, furnace temperature, and LNG consumption. Calculations are performed to determine gas flow, airflow, Qinput, Qthermal, AFR, and burner efficiency in each zone (H2-D and H2-W). In addition, thermal analysis was performed on various insulating materials such as ceramic fiberboard, calcium silicate, and micropore silica to assess their effect on heat loss due to conduction and radiation. The results show that burner efficiency is not always directly proportional to the theoretical AFR value. In the H2-D zone with a relatively high AFR (12.55–15.56), the efficiency reached 69%–82%, while in the H2-W zone with a lower AFR (10.86–11.96) the efficiency decreased to 59%–63%. In addition, in some zones such as zones 1, 7, and 8, there is an aberration of the air-gas ratio from the ideal value, with the average airflow being lower than the theoretical standard. From the thermal side, the use of insulation materials with low conductivity such as microporous silica is able to reduce heat loss by more than 80% compared to standard materials. Increased insulation thickness has also been shown to reduce heat loss by up to 50%, especially in areas with high heat exposure.